PROFIL KELUARGA ANAK-ANAK BERMASALAH - Budi Andayani (Faculty of Psychology, Universitas Gadjah Mada, 2000)
Family has a responsibility in child’s well being, physically and psychologically. Family has important roles in educating and socializing children. It is the families a counselor should examine when children have problems with their life such as personality, or educational problems. The present research is aimed to make family profiles of children with such problems, on the basis of system approach. The profile is made on the basis of family characteristics as a system: family boundary, family rules, and sub-system interaction. The data was collected from Psychological Consulting Office of the Faculty of Psychology GMU. The information was obtained through in-depth interview as a part of counseling process, done by the researcher as a counselor. Fourteen cases then were content analyzed. The result shows that the families of the problematic children are characterized by: (1) vague or widely open family boundaries caused by relationships with extended families; (2) confusing if not inadaptive family rules; and (3) isolations, coalitions, low intensity, lesser warm and close relationships of family sub-systems. Keywords: family profile – system approach